Przegląd środków chemicznych stosowanych w zimowym utrzymaniu dróg w Polsce = Overview of chemicals applied to winter road maintenance in Poland - Czarna, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the basic action taken in the framework of winter road maintenance is the removal of snow and winter slipperiness with the use of abrasive materials or fluxes for surface de-icing or both methods jointly.
Keywords: środki chemiczne; zimowe utrzymanie dróg; śliskość zimowa; chemical agents; winter road maintenance; winter slippery